Proceedings of the 2010 International Conference on E-Business Intelligence 2010
DOI: 10.2991/icebi.2010.58
|View full text |Cite
|
Sign up to set email alerts
|

BI as a service: an attempt to understand the leading adoption factors

Abstract: The research question of this study attempts to identify which are the leading factors for the adoption of a sourcing Software as a Service model for Business Intelligence applications. The objective is to build a model containing enabling factors for the adoption of BI solutions. We seek to expand on the Benlian et al. model [1] which is based on a theoretical framework including axioms from Transaction Cost Theory, Resource Based View, Theory of Planned Behavior. In order to better understand the phenomenon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Ma argued that computer-supporting collaborative learning and social creativity were key terms for designing work with critical reflection in examining consumers’ behaviors in social network services 31,32. Marco et al identified a misalignment observed in using social network services based on a comprehensive literature review on the effect of website designed tools 33. The IBM team suggested that it was a core competing strategy to maintain a visually impressive effective website in today’s marketplaces 34.…”
Section: Introductionmentioning
confidence: 99%
“…Ma argued that computer-supporting collaborative learning and social creativity were key terms for designing work with critical reflection in examining consumers’ behaviors in social network services 31,32. Marco et al identified a misalignment observed in using social network services based on a comprehensive literature review on the effect of website designed tools 33. The IBM team suggested that it was a core competing strategy to maintain a visually impressive effective website in today’s marketplaces 34.…”
Section: Introductionmentioning
confidence: 99%